Effects of Covid -19 Pandemic on Tourism in Kashmir - SHOWKAT AHMAD DAR; NASEER AHMAD LONE (RADJA PUBLIKA, 2022)
Tourism is defined as leisure travel. Tourism generates jobs and promotes long-term growth, benefiting local economies. The Mughal emperor Jahangir called it